2014
DOI: 10.1111/cdoe.12128
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss, periodontal disease, and cognitive decline in the Atherosclerosis Risk in Communities (ARIC) study

Abstract: Objective The purpose of this prospective study was to investigate whether poor oral health predicted eight-year cognitive function change in predominantly late middle adults in the Atherosclerosis Risk in Communities (ARIC) study. Methods Participants included a subset of ARIC participants aged 52–75 years at 1996–1998 from two study sites: Forsyth County NC and Jackson MS. All subjects completed cognitive function assessments both in 1996–1998 and 2004–2006, and the same subjects received a dental examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 35 publications
1
110
0
Order By: Relevance
“…It has been suggested that sites of periodontal infection could be significant sources of inflammatory mediators and bacterial components, which may enter the central nervous system and cause neuronal damage . Although the evidence supporting the potential association between periodontitis and cognitive impairment is increasing, the results from previous studies are not consistent with those from several studies that did not find any significant association between periodontitis and cognitive impairment. It should be noted that there is not enough evidence to draw definite conclusions; additional well‐designed research is warranted in this field.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been suggested that sites of periodontal infection could be significant sources of inflammatory mediators and bacterial components, which may enter the central nervous system and cause neuronal damage . Although the evidence supporting the potential association between periodontitis and cognitive impairment is increasing, the results from previous studies are not consistent with those from several studies that did not find any significant association between periodontitis and cognitive impairment. It should be noted that there is not enough evidence to draw definite conclusions; additional well‐designed research is warranted in this field.…”
Section: Discussionmentioning
confidence: 91%
“…A putative link between periodontitis and cognitive impairment/dementia has been reported . There are several possible underlying mechanisms for this association.…”
Section: Introductionmentioning
confidence: 99%
“…This prospective cohort study of an elderly Japanese population demonstrated an inverse association between number of remaining teeth and risk of development of all‐cause dementia and AD, indicating that subjects with greater tooth loss were at greater risk of onset of dementia. Tooth loss was estimated using data from clinical oral examinations performed by dentists, and dementia subtypes were determined on the basis of brain morphological data (neuroimaging and neuropathology), unlike previous studies . The present prospective cohort study investigated the association between tooth loss evaluated through a professional oral examination and risk of dementia and its subtypes in an elderly general population.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of DD include: Tooth loss, local and/or generalized periodontal detachment, improper operative or prosthetic restorations, and orthodontic managements and the unavoidable consequence of impaired mastication. These DDs may cause sensory and motor cortical reorganization [1–4], affect cerebral functional streams toward multisensory hubs [5,6], impair gustatory, auditory and olfactory perceptions [7–11], and result in memory and cognition impairment [12–30].…”
Section: Introductionmentioning
confidence: 99%
“…The greatest risk factor for cognitive decline and Alzheimer's disease in older adults is age itself [31,32]. Accumulating scientific evidence has indicated a correlation between DD and impaired brain functions such as memory loss, cognitive impairment, and even prodromes of AD and dementia [12–30]. A recent review of both animal trials and clinical research [33] has highlighted the causal relationship of mastication on cognitive functions.…”
Section: Introductionmentioning
confidence: 99%